The Historical Connections of the Soviet Invasion of Afghanistan (Czech Journal of International Relations, 2002)
The Soviet invasion of Afghanistan is among the important milestones of post-war (WWII) development of international relations. Not only did it let loose the new circle of East-West confrontation, but it represented clear proof of the limits of the possibility to export the Marxist revolution to a different civilisation scope as well. The infiltration of the Marxist ideology and its insensitive enforcement caused the strong resistence of the Afghan people, which led to the inglorious removal of the Soviet army from the country. As the author of the article mentions, the secret documents of the Soviet leadership illustrate the incessantly growing conviction of a fatal mistake, i.e. the Soviet military support for irresponsible Afghan communist leaders, acting in contradiction with organic, through centuries evolving traditions and customs. The Kremlin urgencies to find agreement with the moderate Islamists were by ignored by Kabul’s leaders, although some personal changes had taken place. This incompetence led to the final decline of the communist regime.But the pendulum, set in motion by the Marxist coup d’état in 1978, was swinging to the opposite side by this point. The following development in the country caused a new security risk, which has created a challenge for the West. The West now represents Evill in the minds of Islamists, who were deeply hurt during the Soviet invasion by the attack of a foreign power.